2018
DOI: 10.1159/000486161
|View full text |Cite
|
Sign up to set email alerts
|

Potential Interactions of Medication Prescribed in Discharge Letters from a Clinic for Hematology and Oncology

Abstract: Background: As there are few data worldwide concerning the frequency and relevance of interactions of prescribed drugs in hemato-oncology, we analyzed the medication prescribed to patients at a clinic within a comprehensive cancer center. Methods: Details of the medication prescribed for all patients in 2011 were extracted from their discharge letters. All potential medication combinations were assess with respect to the risk of interaction using 3 specialized websites. Results: The files of 202 patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This might partly cause a higher rate of patients affected by drug interactions in our study. Another reason might be a difference in mean age of the patients: 61 years in our study compared to 56 in the study from Schaefer et al (2018). A higher mean age might result in a polypharmaceutical situation with a higher number of Table 5 Likely interactions between CAM supplements and concomitant diseases' treatment in 13 patients a Ginger: increased bleeding risks (e.g.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…This might partly cause a higher rate of patients affected by drug interactions in our study. Another reason might be a difference in mean age of the patients: 61 years in our study compared to 56 in the study from Schaefer et al (2018). A higher mean age might result in a polypharmaceutical situation with a higher number of Table 5 Likely interactions between CAM supplements and concomitant diseases' treatment in 13 patients a Ginger: increased bleeding risks (e.g.…”
Section: Discussionmentioning
confidence: 82%
“…Schaefer et al ( 2018 ) discovered that 47% of 202 hematological cancer patients had at least one potentially interacting drug combination, which is more than discovered in other studies (e.g. Castro-Manzanares et al 2019 ; Hoemme et al 2019 ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Several studies in hematological patients have have shown that potential drug-drug interactions (pDDI's) were frequent ranging from 50 % to 100 % of the patients [14][15][16][17], and that many were of pharmacokinetic origin [14][15][16]. The clinical relevance, variable according the studies, was estimated as major in 62 % [15] and 82 % [18] of the patients, and as moderate in 86 % of the patients [14], 38 % [15].…”
Section: Introductionmentioning
confidence: 99%